2017
DOI: 10.18632/genesandcancer.154
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights: Suppression of EGFR and AKT activation by a small molecule in non-small cell lung cancer

Abstract: Epidermal growth factor receptor (EGFR) activation events and the mammalian target of rampamycin (mTOR) are considered important therapeutic targets in alleviating cancer conditions. The current treatment paradigm has shifted to personalized treatment strategies with tyrosine kinase inhibitors (TKIs) or anaplastic lymphoma kinase (ALK) inhibitors, due to low survival rates in non-small cell lung cancer (NSCLC) in terms of the prevailing platinum-based therapy. In the present study, we examined the anticancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Successful penetration of the BBB by meningitis-causing bacterial pathogens requires four prerequisites: a high level of bacteremia, bacterial adhesion and invasion of BMECs, actin cytoskeleton rearrangement, and bacterial vitality maintenance (Kim, 2002, 2008; Kim et al, 2005; Coureuil et al, 2017); all of which are complex bacteria-host interactions involving multiple host molecules. EGFR is a host factor that has been found to play essential roles in several bacterial infections recently, although it was widely reported previously to be associated with different cancers (Mikami et al, 2005; Yan et al, 2009; Adams et al, 2017; Araki et al, 2017; Chandrasekaran et al, 2017; Dheeraj et al, 2017). For instance, H. pylori was shown to induce EGFR transactivation in gastric epithelial cells, resulting in the upregulation of MMP10 and extracellular matrix disorder (Yan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Successful penetration of the BBB by meningitis-causing bacterial pathogens requires four prerequisites: a high level of bacteremia, bacterial adhesion and invasion of BMECs, actin cytoskeleton rearrangement, and bacterial vitality maintenance (Kim, 2002, 2008; Kim et al, 2005; Coureuil et al, 2017); all of which are complex bacteria-host interactions involving multiple host molecules. EGFR is a host factor that has been found to play essential roles in several bacterial infections recently, although it was widely reported previously to be associated with different cancers (Mikami et al, 2005; Yan et al, 2009; Adams et al, 2017; Araki et al, 2017; Chandrasekaran et al, 2017; Dheeraj et al, 2017). For instance, H. pylori was shown to induce EGFR transactivation in gastric epithelial cells, resulting in the upregulation of MMP10 and extracellular matrix disorder (Yan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Akt, a canonical downstream effector of the EGFR pathway, is important for BoHV-1 infection in MDBK cells [35][36][37], but its role during virus infection in A549 cells has been unknown. To address this question, we initially detected whether Akt signaling was activated in BoHV-1-infected A549 cells.…”
Section: The Activation Of Akt Signaling In Bohv-1-infected A549 Cellmentioning
confidence: 99%
“…There is increasing evidence to suggest that β-catenin is upregulated in NSCLC tumor cells when compared to normal cells. It has been shown that activation of the β-catenin pathway stimulates proliferation and leads to the generation and development of NSCLC 35,36 . In the present study, we showed that AS-IV inhibited the Akt phosphorylation and subsequent GSK-3β function, which in turn stimulated the ubiquitination of β-catenin.…”
Section: Discussionmentioning
confidence: 99%